The Early History of Preventive Conservation in Great Britain and the United States (1850–1950) - Simon Lambert (CeROArt : Conservation, Exposition, Restauration d'Objets d'Art)
The early history of preventive conservation is characterized by the progressive integration of science into the museum world and the strengthening of collaboration between curators, conservators and scientists. This article traces the development of this discipline in Great Britain and in the United States, examining the role played by museum controversies, public debates, and pre- and post-war efforts, between 1850 and 1950.